Administrative Sanctions in The Form of Revocation of Mining Business License Through Investment Arrangement Policy in Indonesia - Arthesya Wiliananda Putri; Maryano; Muthia Sakti (Novateur Publications, 2023)
Prior to the existence of Law Number 3 of 2020, control of minerals and coal by the state was carried out by the Government and/or Regional Governments. After the amendments were made, control of minerals and coal by the state was held by the Central Government, so that currently the authority to revoke mining business licenses belongs to the Central Government, namely the President who is assisted by the Vice President and Ministers. The aim of the research is to analyze the development of the latest regulations related to the imposition of administrative sanctions in the form of revocation of mining business permits through investment management policies in Indonesia. The research method of this article uses normative legal research methods, examines the current laws and regulations in force in Indonesia, both in the form of laws and implementing regulations. The discussion on laws and regulations focuses on primary legal materials, and secondary legal materials. The authority to revoke business licenses in the field of mineral and coal mining is owned by the Minister of Investment/Head of the Investment Coordinating Board, there are 2 (two) main reasons for revocation of permits, namely Business Actors do not submit work plans and cost budgets, and/or Business Actors The business does not have actual activities for a certain period of time. Fulfillment of the conditions for revocation of a mining business license must be fulfilled, if the procedural and substance requirements are not met, then the decision regarding the revocation of the permit becomes a decision that is null and void. The government must be more careful and mature when preparing appropriate legal regulations regarding license revocation
Keywords: License Revocation; Mining; Policy